The radio spectral energy distribution of infrared-faint radio sources - Herzog, A; Norris, RP; Middelberg, E; Seymour, N; Spitler, LR; Emonts, BHC; Franzen, TMO; Hunstead, R; Intema, HT; Marvil, J; Parker, QA; Sirothia, SK; et al. (EDP Sciences, 2016)
Context.Infrared-faint radio sources (IFRS) are a class of radio-loud (RL) active galactic nuclei (AGN) at high redshifts (z ≥ 1.7) that are characterised by their relative infrared faintness, resulting in enormous radio-to-infrared flux density ratios of up to several thousand.